2009
DOI: 10.2478/v10101-009-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indoor cycling associated with diet on body composition and serum lipids

Abstract: Effects of indoor cycling associated with diet on body composition and serum lipids Study aim: To determine the effects of indoor cycling training combined with restricted diet, lasting 12 weeks, on serum lipid concentrations in obese women. Material and methods: Twenty women aged 23.8 ± 3.6 years were randomly assigned into two groups: control (C) and experimental (E), the latter subjected to indoor cycling at various loads, 3 sessions weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…The results of this study show that cycling workouts are effective in improving cardiorespiratory fitness. The magnitude of the change in VO2max in the current study (by 12.51%) is comparable with data from previous studies [2,14,23,24,25,27]. For example, 8-week cycling sessions of moderate and high intensity contributed to an increase of 11-12% in VO2max in female students aged 20-21 years [2].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study show that cycling workouts are effective in improving cardiorespiratory fitness. The magnitude of the change in VO2max in the current study (by 12.51%) is comparable with data from previous studies [2,14,23,24,25,27]. For example, 8-week cycling sessions of moderate and high intensity contributed to an increase of 11-12% in VO2max in female students aged 20-21 years [2].…”
Section: Discussionsupporting
confidence: 89%
“…Together with improved physical fitness, the optimization of anthropometric indices was one of the goals of cycling training, since abdominal obesity, measured based on waist circumference (WC) in combination with BMI, reliably predicts possible health risks. It is known that cycling training is an effective tool for optimizing body composition and reducing BMI [23,24]. Our results show that cycling training carried out according to the proposed program, without any restrictions in the diet, is effective for weight loss and stimulates decreases in WC in young women (of 6.05% on average).…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, a lot of sedentary people participate in this activity in order to lose weight; it is a motivating activity for them. In this sense, Valle et al (2009 ; 2010) reported that indoor cycling associated with a restricted diet is an excellent option in controlling obesity and serum lipids. Bianco et al (2010) found a decrease in body weight, without any restriction on food consumption, and an improvement in cardiorespiratory fitness in young overweight women.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which the resistance or endurance training leads to decreased fat mass is related to the increase in the metabolism, energy usage, and enzymatic processes involved in fat metabolism. In this respect, an increase in lipoprotein lipase activity has been reported (21). One limitation of the present study was that the lipoprotein lipase changes were not measured.…”
Section: Discussionmentioning
confidence: 65%